Supportive evidence for FOXP1, BARX1, and FOXF1 as genetic risk loci for the development of esophageal adenocarcinoma. (15th August 2015) - Becker, Jessica; May, Andrea; Gerges, Christian; Anders, Mario; Veits, Lothar; Weise, Katharina; Czamara, Darina; Lyros, Orestis; Manner, Hendrik; Terheggen, Grischa; Venerito, Marino; Noder, Tania; et al.
Abstract: The Barrett's and Esophageal Adenocarcinoma Consortium (BEACON) recently performed a genome‐wide association study (GWAS) on esophageal adenocarcinoma (EAC) and Barrett's esophagus. They identified genome‐wide significant association for variants at three genes, namely CRTC1, FOXP1, and BARX1 . Furthermore, they replicated an association at the FOXF1 gene that has been previously found in a GWAS on Barrett's esophagus. We aimed at further replicating the association at these and other loci that showed suggestive association with P < 10 −4 in the BEACON sample. In total, we tested 88 SNPs in an independent sample consisting of 1065 EAC cases and 1019 controls of German descent. We could replicate the association at FOXP1, BARX1, and FOXF1 with nominal significance and thereby confirm that genetic variants at these genes confer EAC risk. In addition, we found association of variants near the genes XRCC2 and GATA6 that were strongly ( P < 10 −5 ) although not genome‐wide significantly associated with the BEACON GWAS. Therefore, both variants and corresponding genes represent promising candidates for future EAC association studies on independent samples. Abstract : We followed up 88 SNPs which showed association in a genome‐wide association study on esophageal adenocarcinoma (EAC). Our screening sample comprised 1065 EAC cases and 1019 controls. The study provides supportive evidence that SNPs near FOXP1, BARX1, and FOXF1 confer EAC risk. In addition, we found association at XRCC2 and GATA6 representing new and promising candidates for future studies on EAC.